Preparing for future K-workers: a study in determining computer competency among students at UiTM Malacca / Jamal Ludin - Ludin, Jamal (2003)
The study is on "Preparing for Future K-workers: A Study in Determining Computer Competency Among Students at UiTM Malacca. This study also to determining, identify and conclude the related factors that contribute to determining the level of computer competency such computer knowledge, computer competency, computer subject, factors influencing and the barriers factors to the level of computer competency among the Bachelor degree students in UiTM Malacca. This study also concentrates on Bachelor degree students as respondents as the future K-workers who have the standards level of computer competency and skills. The bachelors' degree students will graduate in with a standard level of computer competency and skills of using tools of Information Technology. The findings determine the level of computer competency among Bachelor degree students as the respondents by analyzing the variables related on it. The study involves 70 the Bachelor degree students by doing survey and fields interview and interpreted data from it. The results of this study show that the Bachelor degree students have sufficient knowledge in IT basic. They also having low-level Computer Competency and skills will abuse in preparing future K-workers will lead not knowledgeable-workers when they graduate. At the end of the study, the researcher has proposed the recommendations to the UiTM's management, academicians and the Bachelor degree students towards preparing the More K-workers in determining the level of Computer Competency in using Information Technology that certified by the authority concern for the undergraduates.